2022
DOI: 10.1084/jem.20211422
|View full text |Cite
|
Sign up to set email alerts
|

Activating NO–sGC crosstalk in the mouse vascular niche promotes vascular integrity and mitigates acute lung injury

Abstract: Disruption of endothelial cell (ECs) and pericytes interactions results in vascular leakage in acute lung injury (ALI). However, molecular signals mediating EC–pericyte crosstalk have not been systemically investigated, and whether targeting such crosstalk could be adopted to combat ALI remains elusive. Using comparative genome-wide EC–pericyte crosstalk analysis of healthy and LPS-challenged lungs, we discovered that crosstalk between endothelial nitric oxide and pericyte soluble guanylate cyclase (NO–sGC) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…3B ). These results align with previous studies showing that sGC is required to suppress the expression of inflammatory cytokines in the pericytes of the lung and liver (Flores-Costa et al, 2018 ; He et al, 2023 ; Yang et al, 2021 ). The downregulated genes in pericytes were involved in an extracellular matrix organization and cell–matrix adhesion (Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…3B ). These results align with previous studies showing that sGC is required to suppress the expression of inflammatory cytokines in the pericytes of the lung and liver (Flores-Costa et al, 2018 ; He et al, 2023 ; Yang et al, 2021 ). The downregulated genes in pericytes were involved in an extracellular matrix organization and cell–matrix adhesion (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies have demonstrated that the NO receptor sGC is specifically expressed in the pericytes of healthy vessels in various organs, including the brain, retina, lung, liver, and muscle, with diverse functions ranging from maintaining vascular integrity to contributing to tissue fibrosis (Bettaga et al, 2015 ; Friebe and Englert, 2022 ; Fukutani et al, 2009 ; He et al, 2023 ; He et al, 2016 ; Yang et al, 2021 ). However, the expression pattern and function of sGC in tumors have not been characterized.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations